Using HFACS to understand human error in railway dispatcher performance: a study of proactive safety inspection records. - Guo, Zizheng; Pang, Huishan; Zhang, Jingyu; Zhang, Jun; Wang, Jiazhe; He, Chuanning; Li, Chengen (Ergonomics, 2025)
This study analyzes 4,095 proactive safety inspection records obtained from a large dispatching centre by utilising the HFACS framework. These proactive safety inspection records offer comprehensive documentation of incidents, capturing major accidents and numerous minor discrepancies and lapses that often go unnoticed in accident reports. The analysis revealed that most incidents were attributed to unsafe actions, primarily skill-based errors and poor decision-making. Additionally, contributing factors such as adverse mental states, personal readiness, and crew resource management were found to play a significant role as preconditions for unsafe acts. Path analyses further established a significant correlation between factors such as unsafe supervision, preconditions for unsafe acts, and the occurrence of unsafe acts. In our discussion, we critically evaluate the strengths and limitations of proactive safety inspection records in safety research. Moreover, we emphasise these findings' potential to enhance safety within the railway industry. PRACTITIONER SUMMARY: Based on a substantial dataset comprising proactive safety inspection records of railway dispatchers rather than the incident reports utilised in prior studies, this paper presents a causal model of human error among railway dispatchers in combination with HFACS and critically evaluates the strengths and limitations of active safety inspection records.